1998
DOI: 10.1074/jbc.273.45.29417
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Activation of Nuclear Transcription Factor-κB in Marrow Macrophages Is Mediated by c-Src Tyrosine Phosphorylation of IκBα

Abstract: Tumor necrosis factor-␣ (TNF) exerts its transcriptional effects via activation of nuclear transcription factor-B (NF-B). NF-B is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 60 publications
8
114
0
2
Order By: Relevance
“…Tyrosine kinases of the src family also activate NF-kB at the level of IkB phosphorylation (Imbert et al, 1996;Abu-Amer et al, 1998;Takada et al, 2003). Only ectopic expression of Bcr-Abl suppresses TNF-induced NF-kB activation due to downregulation of TNFRs and subsequent inhibition of IkBa degradation (Mukhopadhyay et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine kinases of the src family also activate NF-kB at the level of IkB phosphorylation (Imbert et al, 1996;Abu-Amer et al, 1998;Takada et al, 2003). Only ectopic expression of Bcr-Abl suppresses TNF-induced NF-kB activation due to downregulation of TNFRs and subsequent inhibition of IkBa degradation (Mukhopadhyay et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…TNFa-induced NF-kB activation is mediated by various nonreceptor kinases that phosphorylate inhibitor kB (IkB) or p65 at serine residues (Vermeulen et al, 2003). In addition, tyrosine phosphorylation has been implicated in TNFa-induced activation of NF-kB (Imbert et al, 1996;Abu-Amer et al, 1998;Takada et al, 2003). Upon inhibition of TNFa-induced NF-kB activation, for example, by ultraviolet light and cytotoxic agents such as daunorubicin (Campbell et al, 2004), TNFa becomes a potent inducer of apoptosis (Karin and Lin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The role of c-Src in TNF-induced NF-B activation has been demonstrated (21,23). It has been shown that c-Src causes the tyrosine phosphorylation of I B kinase-␤ needed for TNF-induced NF-B activation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Proline-rich tyrosine kinase (Pyk2) 3 (18,19) and p53/Lyn p56 (20) have roles in TNF-induced neutrophil activation; Etk/Bmx in TNF-induced endothelial cell migration and angiogenesis; c-Src in TNF-induced NF-B activation in the marrow macrophages (21,22); and TNF in regulation of gap junctions in airway epithelial cells (23). Pyk2 has also been implicated in TNF-induced JNK activation (24).…”
Section: Tnf Activates Syk Proteinmentioning
confidence: 99%
“…It is probable that PKC/c-Src lies downstream of TRAF2, because the findings that c-Src acts downstream of TRAF in response to TNF-related activation-induced cytokine or IL-2 in osteoclasts, dendritic cells (29), or 293 cells (30) have been reported. c-Src is involved in NF-B activation in bone marrow macrophages, U937 cells, and B cells (31)(32)(33). In bone marrow macrophages, TNF-␣ induces activation of c-Src, which associates with I-B␣ and phosphorylates Tyr 42 of I-B␣, leading to NF-B activation and IL-6 release (31).…”
Section: Discussionmentioning
confidence: 99%